Minimum Quantity Lubrication: Quantifying Non-Deterministic Component Of Sustainability Index For Machining Operations - Najiha, M. S.; M. M., Rahman; K., Kadirgama (Universiti Malaysia Pahang, 2016)
Sustainable manufacturing is pursued to achieve the long-term sustainable development of manufacturing systems. In practice, the sustainability of any system is difficult to assess because of uncertain factors involved in the sustainability study. Experts have defined a sustainability index in order to define any system. This sustainability index consists of two components, namely the deterministic component and non-deterministic component. The nondeterministic component consists of the contributing factors of societal, environmental, and economic effects. On account of the uncertainties involved and the non-quantifiable nature of the non-deterministic component, fuzzy logic is used to assess the non-deterministic component. In this paper the nondeterministic component of the sustainability index for a machining process with Minimal Quantity Lubrication is calculated using fuzzy logic. The basic objective of this study is to quantify the non-deterministic component of the sustainability index by using a fuzzy rule-based model for the anticipation and functional analysis of machining with minimal quantity lubrication.